FAMILY CAREGIVER-BASED PREVENTION AMONG AMONG LEPROSY PATIENTS IN SAMPANG DISTRICT: FAMILY CAREGIVER INDEPENDENCE THAT CARING FOR LEPROSY PATIENT - Achmad Ali Basri; Rachmat Hargono; Elida Ulfiana; Merryana Adriani; Retno Indarwati; Setho Hadisuyatmana; Nina Agustina (International Journal of Nursing and Health Services (IJNHS), 2019)
Disease with high stigma, leprosy has a totality effect in patient life. Families are components that a higher risk of contracting leprosy. Purpose of study to get prevention strategies for family caregiver that caring for leprosy patient based on culture in sampang district. A qualitative with phenomenology approach was applied in this study. We conducted the in-depth interview, group discussion forum and expert discussion to explore themes. Using the Collaizi analysis, 15 participants based on the saturation data were selected in this study. The results showed those 2 themes and 4 sub-themes in the study. The first themes such as discipline treatment with sub themes were medication adherence and prohibition during treatment. The second theme such as disease course with sub themes were perceived symptoms and treatment experience. Prevention family caregiver based in culture approach is needed for nurses and family caregiver, improve caring for leprosy patients’ ability. Keywords: Family caregiver, Transcultural Nursing, Leprosy, Phenomenology Study